Mobile Learning Media for Enhanced Motivation in Audio and Video Processing: A Vocational Multimedia Approach - Fadilah, M. Nuran; Ahmad, Azhar; Yunus, Yunus (Letters in Information Technology Education (LITE), 2024)
activities to be replaced by technology. Based on the results of observations and initial observations made at SMKN 1 Pasuruan, at SMK PGRI 8 Malang, and at SMKN 3 Kota Bima, a problem was found, namely difficulties in understanding the material in the subject of Audio and Video Processing Engineering because the media was lacking. The objectives of the research activities were to develop mobile-based learning media, describe learning media, analyze the feasibility of learning media, and describe the level of student learning motivation. The developed learning media is stored in .apk format so that it can be operated on a smartphone. The learning media development model adapts the Plomp development model, consisting of an initial investigation or preliminary research phase, a development or prototyping phase, and an assessment phase. In the initial investigation phase or preliminary research, analyze the learning of audio and video processing techniques and find a problem. Then, in the development or prototype phase, there were validation results from media experts of 91.31 per cent and results from material experts of 93.3 per cent. Finally, in the testing phase of the field test on 26 students, the results were 86.71 per cent, and the measurement of learning motivation was 82.85 per cent. Referring to the results of the research, the implementation of the mobile-based learning media that was developed is very feasible to be applied in the learning process. It is quite efficient and effective in increasing student learning motivation